Pengaruh Corporate Social Responsibility (CSR) dan Karakteristik Perusahaan terhadap Praktik Penghindaran Pajak Perusahaan yang Terdaftar di Bursa Efek Indonesia - Androni Susanto; Veronica (Politeknik Ganesha Medan, 2022)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and company characteristics on corporate tax avoidance. The sampling technique used was purposive sampling. The sample of this research is the financial statements and sustainability reports of 73 companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The analytical method used is multiple linear regression. The results of this study indicate that CSR has a significant positive effect on current taxes, which means that companies that are responsible to stakeholders tend to avoid tax avoidance practices or pay more taxes. CSR, ROA and firm size have a significant negative effect on tax avoidance. Leverage and intangible assets have a significant positive effect on tax avoidance. Other company characteristics variables such as fixed assets, operating cash flow, sales growth have no significant effect on tax avoidance.